Perbuatan Melawan Hukum terhadap Hak Cipta Lagu oleh Korporasi (Studi Kasus Putusan Nomor 19/Pdt.Sus-Hakcipta/2020/Pn.Niaga.Jkt.Pst dan Putusan Nomor 4/Pdt.Sus-Hki/Hakcipta/2020/Pn.Niaga.Sby) - Denny Hartono; Sardjana Orba Manullang; Anwar Budiman (LPPM Universitas Ekasakti Padang, 2023)
Legal protection for song copyrights is needed in order to create a better climate and atmosphere for the growth and development of music in Indonesia. The problem is how is the form of legal protection for song copyright holders for unlawful acts committed by corporations? What are the considerations of legal reasons and legal philosophical considerations by the Panel of Judges regarding Tort Towards Song Copyright by Corporations in the Court Ruling of the Central Jakarta District Court Number 19/Pdt.Sus-HakCipta/2020/PN.Niaga.Jkt.Pst. and Court Ruling of the Surabaya District Court Number 4/Pdt.Sus-HKI/HakCipta/2020/PN.Niaga.Sby.? Normative juridical research methods. In conclusion, legal protection for Tort toward song copyright by corporations. If there is a song copyright dispute, the settlement can be carried out through alternative dispute resolution, arbitration, a court where the court is a commercial court. The decision on the lawsuit must be pronounced no later than 90 (ninety) days after the lawsuit is registered. Therefore, the task of the judge to try cannot be separated from legal discovery activities. In the court decision verdict number 4/Pdt.Sus-HKI/HakCipta/2020/PN.Niaga.Sby. November 12, 2020, which rejected the Plaintiff's lawsuit in its entirety, is inappropriate because the Panel of Judges should carry out legal discovery activities by looking at Government Regulation Number 20 of 2017 Concerning Import or Export Control of Goods Allegedly Consisting of or Originating from Intellectual Property Rights Violations.